Fangers opplevelser av skam og stolthet etter soning - Svennevig, Haukland, Tallaksen, Diverse: (Nordisk Tidsskrift for Kriminalvidenskab, 2016)
English title: Prisoners’ self-perceived shame and pride after imprisonment The aim of this study is to examine former prisoners’ experiences of shame in life after imprisonment, and how processes of change from shame to pride take place. Qualitative in-depth interviews are conducted with seven former prisoners affiliated with the self-help organization WayBack. The empirical material is processed using content analyses. A hermeneutic phenomenological framework inspired the study. The study shows that the movement from shame to pride is closely related to empowerment and to a change from marginalization to integration. The analysis reveals that shame is activated by society’s limited acknowledgement of ex-prisoners. Social arenas of equals can be experienced as essential to create new identities and a sense of empowerment. Acknowledging that change requires acceptance of help from others – as well as provision of help to others, appears to be an important facilitator of change from shame to pride. The individual’s opportunity to put words into feelings is central. Likewise, the achievement of coherence in the world (SOC) is of crucial importance. The importance of being recognized and achieving social value are also key findings of the research.